Performance Comparison of Tilt Integral Derivative (TID) Controller and Proportional Integral Derivative (PID) Controller for Parabolic Dish Antenna System - Inah, Obi Mathias; Nazif, D. M.; Umar, Sadik; Muhammad, Fatima; Bal., Yakubu Barau (Darul Yasin Al Sys, 2025)
This study presents a comparative performance analysis of Proportional-Integral-Derivative (PID) and Tilt-Integral-Derivative (TID) controllers in the context of azimuth positioning for a parabolic dish antenna system. A detailed system model was developed in MATLAB/Simulink, integrating key components such as motor dynamics, amplifier behavior, potentiometer-based feedback, and gear mechanisms. The performance of both controllers was evaluated under ideal conditions and in the presence of environmental disturbances, with wind effects modeled using the Dryden wind turbulence model to simulate real-world scenarios. Key performance metrics, rise time, settling time, overshoot, and steady-state error were used to assess controller efficacy. The results indicate that the PID controller outperforms the TID controller in terms of stability, accuracy, and resilience to disturbance. Although the TID controller exhibited a marginally faster initial response, it suffered from greater overshoot and reduced stability, particularly under wind-induced disturbance. These findings underscore the robustness and suitability of PID control for high-precision antenna positioning systems, while also suggesting that enhancements to TID control may be possible through optimization techniques or hybrid controller designs.